MODEL PENANGGULANGAN BENCANA DI KAWASAN TAMAN NASIONAL GUNUNG LEUSER DALAM PERSFEKTIF POLITIK EKOLOGI - ANWAR SARAGIH (Program Magister Ilmu Politik, Universitas Diponegoro, 2016)
Abstrac One of the most worrying issues in the 21st century, in addition to the economic crisis and political crisis is the environmental crisis. Because the impact of environmental damage could result in catastrophic disasters such as smoke, landslides, flooding to the disaster smoke. Langkat district of North Sumatra has clearly felt the impact of forest destruction in the area of Gunung Leuser National Park. Where in the past 12 years since the 2003-2015 experience regular flooding. Especially flash floods that hit Langkat particularly Bahorok subdistrict Subdistrict Besitang 2003 and 2006. For many years flood in Langkat had not yet found a model appropriate measures in addressing floods in langkat.Berbagai policy, regulation and the model has not been able to alleviate problems in the Gunung Leuser National Park in particular Illegal logging, forest perampahan and land conversion. This study aims to find the right model Countermeasures in dealing with disasters in langkat deforestation in the area of Gunung Leuser National Park with the perspective of Political Ecology. This study also examines the major trouble spots in the last 12 years why not also found the model appropriate measures in disaster management in the area of Gunung Leuser National Park. This study is a qualitative research by using a critical paradigm, and this research is a Model Scheme for Disaster Management in the Region Gunung Leuser National Park in the Perspective of Political Ecology.